Hierarchical Silica Inverse Opals as a Catalyst Support for Asymmetric Molecular Heterogeneous Catalysis with Chiral Rh‐diene Complexes. Issue 9 (18th March 2021) - Deimling, Max; Kousik, Shravan R.; Abitaev, Karina; Frey, Wolfgang; Sottmann, Thomas; Koynov, Kaloian; Laschat, Sabine; Atanasova, Petia
Abstract: The efficacy of heterogeneous catalysis relies heavily on diffusion and distribution of reactants within catalyst supports. However, the presence of confinement, essential for reaction selectivity, drastically slows down molecular transport. Here, macro‐mesoporous silica inverse opal (SiO2 −IO) films were used as a model system to study the rather unexplored molecular infiltration behavior using a probe molecule resembling a catalyst via confocal laser scanning microscopy (CLSM). CLSM analysis revealed homogeneous tracer distribution in SiO2 −IO and attachment to both transport and mesopores. Bulk macro‐mesoporous SiO2 −IO support was used for the attachment of mono‐ and bis‐functionalized chiral Rh‐diene complexes, and the catalytic activity and selectivity with respect to the support was studied. Lower enantioselectivity was observed with the bis‐functionalized ligand due to ligand entanglement and reduced accessibility of the active site, while the mono‐functionalized ligand gave an excellent enantioselectivity of 94 % ee in the asymmetric 1, 2‐addition of triphenylboroxine to N‐ tosylimines and could be recycled up to three times. Abstract : Molecular infiltration : Spatial distribution and tethering sites of catalyst‐resembling probe molecules in macro‐mesopores silica inverse opal (SiO2 −IO) films were studied via confocal laser scanning microscopy. Bulk macro‐mesoporous SiO2 −IOs were further used for attachment of mono‐ and bis‐functionalized chiral Rh diene complexes, and the catalytic activity and selectivity with respect to the porous material was studied in the asymmetric 1, 2‐addition to N ‐tosylimines.